Training and Development of Business Instructors in Relation to Faculty Performance - Pallega, Lovelle P. (Future Science / FSH-PH Publications, 2022)
The study aims to describe the relationship between trainings and development of business educators and their performance in one of the state universities in Zamboanga Peninsula. Data mining technique was used in determining the profile of business educators, the number of seminars and trainings attended, and performance rating. Business instructors included the part-time, temporary and permanent faculty members. Results of the study revealed that faculty received more trainings related to instructions but very few in research, extension and production. Business educator’s performance were mostly very satisfactory across the four core functions despite the limited number of trainings received on some functions particularly to the new and young faculty. Further, there is a significant difference on the performance rating based on their employment status. However, study reveals that trainings and development have no significant relationship with performance. The study provides significant managerial implications on the evaluation of faculty performance and highlights the need to develop a framework for training and development. Moreover, the study recommends the need for the administration to revise its performance evaluation tool to obtain a more concrete and objective analysis in gauging how well the university performs in achieving its goals and targets.